Current Advance of Therapeutic Agents in Clinical Trials Potentially Targeting Tumor Plasticity - Yang, Xiao-Guang; Zhu, Lan-Cao; Wang, Yan-Jun; Li, Yan-Yu; Wang, Dun (Frontiers in Oncology, 2019)
Tumor plasticity refers to tumor cell’s inherent property of transforming one type of cell to different types of cells. Tumor plasticity is the main cause of tumor relapse, metastasis and drug resistance. Cancer stem cell (CSC) model embodies the trait of tumor plasticity. During carcinoma progression, epithelial-mesenchymal transition (EMT) plays crucial role in the formation of CSCs and vasculogenic mimicry (VM) based on epithelial-mesenchymal plasticity. And the unique tumor microenvironment (TME) not only provides suitable niche for CSCs but promotes the building of CSCs and VM that nourishes tumor tissue together with neoplasm metabolism by affecting tumor plasticity. Therapeutic strategies targeting tumor plasticity are promising ways to treat malignant tumor. In this article, we discuss the recent developments of potential drug targets related to CSCs, EMT, TME, VM and metabolic pathways and summarize drugs that target these areas in clinical trials.